1985
DOI: 10.1021/la00066a001
|View full text |Cite
|
Sign up to set email alerts
|

C2Hn fragments on metal surfaces

Abstract: The chemisorption of an acetylene (HCCH), a vinylidene (CCH2), and an ethylidyne (CCH3) on metal surfaces, especially Pt(lll), is analyzed in some detail, with an emphasis on the electronic rearrangements ensuing. The bonding is described in terms of semilocalized states, in turn obtained via a deconvolution of the total density of states into fragment orbitals of the hydrocarbon and the surface. The geometrical choices made by the various fragments on surfaces are analyzed by simple perturbation theory. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 4 publications
6
13
1
Order By: Relevance
“…The rc~ mixed lone pair is more stable than the ~ orbital. In contrast, previous theoretical studies (extended Huckel [ 15] and ab-initio [ 13,14]) have found the reverse order, rc being more stable than G. The discrepancy can be attributed to the polarization functions which are missing in the previous ab-initio results. With the Gaussian program, the STO-3G basis set gives the order 7r < rG, whereas the 6-31G** basis set gives the order lr~<~.…”
Section: Acetylene Adsorptioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The rc~ mixed lone pair is more stable than the ~ orbital. In contrast, previous theoretical studies (extended Huckel [ 15] and ab-initio [ 13,14]) have found the reverse order, rc being more stable than G. The discrepancy can be attributed to the polarization functions which are missing in the previous ab-initio results. With the Gaussian program, the STO-3G basis set gives the order 7r < rG, whereas the 6-31G** basis set gives the order lr~<~.…”
Section: Acetylene Adsorptioncontrasting
confidence: 63%
“…Other calculations concern Cu(lll) (HF [14]), Pt(lll) and Rh(lll) (EHT [11,15]), and Pd(lll) (HF [14]). For ethylene adsorption, the available results concern the adsorption on Ni(100) (X, [1637]) and Ni(ll0) (DFT [18]) surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a metal surface " In analogy to our previous studies 1 ' 21 . we find that the charge distribution among the slab layers changes as a function of the number of electrons per metal atom.…”
Section: A21mentioning
confidence: 68%
“…The occupation of the valence s orbitals seems to be slightly lower and that of the p orbitals slightly greater that would have been anticipated. The surface-layer of the slab is negatively charged relative to the bulk due to the greater number of interactions [42].…”
Section: Resultsmentioning
confidence: 99%